Extraction of Coriander Oil Using Twin‐Screw Extrusion: Feasibility Study and Potential Press Cake Applications. (30th June 2015) - Uitterhaegen, E.; Nguyen, Q. H.; Sampaio, K. A.; Stevens, C. V.; Merah, O.; Talou, T.; Rigal, L.; Evon, Ph.
Abstract: This study presents an assessment of the vegetable oil extraction from coriander fruits through mechanical pressing, more specifically twin‐screw extrusion. This comprises an evaluation of the oil recovery obtained and its respective quality, as well as the specific mechanical energy, representing an economical point of view. With regard to the extrusion optimization, the screw configuration, the device's filling coefficient and the pressing temperature were varied. The screw configuration was shown to exhibit a key influence on the extraction efficiency and oil recoveries of at least 40 % were reached when the pressing zone was positioned immediately after the filter and consisted of 50 mm long, reverse screws with a ‐33 mm pitch. Furthermore, with a device's filling coefficient of 39.4 g/h rpm and a pressing temperature of 120 °C, an oil recovery of 47 %, the highest of this study, was reached with concurrent low energy consumption. Next to this, operating parameters of 47.1 g/h rpm and 80 °C resulted in the production of a press cake with the lowest residual oil content (15 %) in this study, although this also involved a significant increase in the filtrate's foot content. All the produced oils were of acceptable quality (<1.5 % acidity), showed high petroselinic acid content (73 %), and were pleasantly scented.